Religious Manipulation in Child Sexual Harassment: Islamic Boarding Schools in Indonesia - Bin Mohamad, Abdul Basir; Nur Hakim, Putri Rahmah; Saputra, Hanif; Jannah, MIftahul; Adli, Muhammad (Nurani, 2024)
Child sexual abuse in Islamic boarding schools in Indonesia remains a pressing issue that is often overlooked within educational institutions. This study investigates the manipulation of religious doctrine in cases of child sexual harassment within these environments, aiming to understand how perpetrators exploit religious principles. The research uses a descriptive qualitative approach and analyzes online media coverage to explore those involved' characteristics, methods, and motives. The findings reveal that perpetrators employ three primary strategies to manipulate religion: redefining religious doctrines, reconstructing religious practices, and repositioning religious authority. These tactics are employed to legitimize and normalize sexual harassment of children in Islamic boarding schools. This study recommends conducting in-depth interviews with perpetrators and victims to gain a deeper and more empirical understanding. Additionally, the study provides recommendations for developing policies and practices to prevent religious manipulation and safeguard children's rights within Islamic boarding schools. This study emphasizes the urgent need for effective measures to protect vulnerable children in these educational settings.